Intoxication with alcohol: An underestimated trigger of Brugada syndrome?. (5th April 2016) - Achaiah, Andrew; Andrews, Neil
Alcohol intoxication is a potentially under-recognised precipitant of Brugada syndrome. Higher pre-cordial electrocardiogram lead placement increases sensitivity of detecting the Brugada pattern.